Single-ion conducting polyion liquid electrolyte and preparation method and application thereof
By using single ion conduction polyion liquid electrolyte in lithium-ion batteries, the covalent connection of borate anionic receptor type crosslinking agent and polyion liquid monomer and Lewis acid fixation technology are used to improve the number of lithium ion migration and the number of lithium ion liquid electrolytes and the use of covalent connection of boric acid ester anionic receptor type crosslinking agent and polyion liquid monomer and Lewis acid fixation technology, the number of lithium ion migration and Battery performance solves the safety hazards of traditional electrolytes and the problems of insufficient battery performance.
Patent Information
- Application Number
- CN202411263898.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-31
AI Technical Summary
The organic carbonate liquid electrolyte used in traditional lithium-ion batteries is flammable and easy to leak. Lithium ion deposition leads to irregular area enrichment, leading to lithium dendrites growth and diaphragm puncture, which poses serious safety hazards, and ionic liquid electrolytes The number of lithium ion migrations of the battery is too low, resulting in poor performance of the high-rate battery.
Using a single ion conduction polyion liquid electrolyte, consisting of borate anionic receptor crosslinking agent, polyionic liquid monomer, crystal plasticizer and lithium salt, the anions are fixed with Lewis acid through covalent bonding, which enhances the anions Lithium ion migration number and in situ thermal polymerization was prepared under solvent-free conditions.
It significantly improves the high-rate performance and room temperature ion conductivity of lithium-ion batteries, enhances the safety and performance of the battery, and solves the problem of too low lithium-ion migration.
Smart Images

Figure CN119230935A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium battery electrolytes, and in particular to a single-ion conducting polyionic liquid electrolyte and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have been widely used in portable electronic devices and even electric vehicles due to their high energy density, long cycle life and environmental friendliness. However, traditional commercial lithium-ion batteries use organic carbonate liquid electrolytes, which are not only flammable, easy to leak and have poor chemical stability, but also prone to irregular regional enrichment distribution during the continuous deposition of lithium ions on the negative electrode, leading to the growth of lithium dendrites, piercing the diaphragm and contacting the positive electrode to cause a short circuit, posing a serious safety hazard. Solid polymer electrolytes have received widespread attention due to their good mechanical properties, thermal stability and processing properties, and are expected to become a new generation of lithium battery electrolyte materials.
[0003] Ionic liquids refer to molten salts below 100°C or at room temperature. They can be considered as a class of liquids composed entirely of anions and cations, and can be composed of a variety of compounds through the selection and design of anions and cations. Polyionic liquids are generated by the polymerization of ionic liquid monomers. Compared with traditional polymers such as polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), etc., polyionic liquids have the advantages of ionic liquids such as good thermal stability, low saturated vapor pressure, and wide electrochemical stability window. At the same time, they have the advantages of excellent flexibility and processability of polymers, and are a very promising polymer matrix material.
[0004] In the related art, an ionic liquid electrolyte is provided, which has become one of the most competitive systems for high-voltage lithium battery electrolytes due to its wide electrochemical window, high room temperature ionic conductivity, and non-flammability caused by extremely low saturated vapor pressure.
[0005] However, the lithium ion migration number of this ionic liquid electrolyte is too low, resulting in poor high-rate performance of the battery and poor performance of the lithium metal negative electrode. Summary of the invention
[0006] The present application provides a single-ion conducting polyionic liquid electrolyte and a preparation method and application thereof, so as to solve the technical problem that the lithium ion migration number of ionic liquid electrolytes in the related art is too low.
[0007] In the first aspect, the present application provides a single ion conducting polyionic liquid electrolyte, which is mainly prepared from a borate anion receptor crosslinker, a polyionic liquid monomer, a crystal plasticizer and a lithium salt;
[0008] The borate anion receptor crosslinking agent is obtained by reacting a borate compound and an acrylate compound;
[0009] The polyionic liquid monomer is composed of anions and cations, and the cation is one of imidazoles, pyrroles, and piperidines containing a carbon-carbon double bond;
[0010] The borate anion receptor crosslinking agent and the cation of the polyionic liquid monomer are connected by a covalent bond.
[0011] In some embodiments of the present application, the structural formula of the cation of the above-mentioned polyionic liquid monomer is:
[0012]
[0013] Wherein, R is methyl, ethyl, propyl or butyl, and n is 1-3.
[0014] In some embodiments of the present application, the structural formula of the borate anion receptor cross-linking agent is:
[0015]
[0016] Wherein, n is 1-10.
[0017] In some embodiments of the present application, the borate ester compound is trimethyl borate or trimethoxyboroxine;
[0018] The above-mentioned acrylate compound is 2-hydroxyethyl methacrylate or polyethylene glycol methacrylate.
[0019] In some embodiments of the present application, the molar ratio of the borate compound to the acrylate compound is 1:3.
[0020] In some embodiments of the present application, the molar ratio of the borate anion receptor crosslinker, the polyionic liquid monomer, the crystal plasticizer and the lithium salt is in the range of 1:(1-9):2:1.
[0021] In some embodiments of the present application, the above-mentioned plasticizer is succinonitrile;
[0022] The above lithium salt is lithium bis(trifluoromethanesulfonyl imide) or lithium bis(fluorosulfonyl imide);
[0023] The anion of the polyionic liquid monomer is a bis(trifluoromethanesulfonyl imide) ion, a bis(fluorosulfonyl imide) ion, a hexafluorophosphate ion, or a tetrafluoroborate ion.
[0024] In a second aspect, the present application provides a method for preparing the above-mentioned single ion conducting polyionic liquid electrolyte, comprising the following steps:
[0025] In the absence of solvent, a borate anion receptor crosslinker, a polyionic liquid monomer, a plasticizer and a lithium salt are mixed, and in situ thermal polymerization is performed under the action of a thermal initiator to obtain a single ion conductive polyionic liquid electrolyte.
[0026] In some embodiments of the present application, the mass of the thermal initiator is 1%-5% of the total mass of the borate anion receptor crosslinker and the polyionic liquid monomer; the reaction temperature of the in-situ thermal polymerization is 60°C-80°C, and the reaction time is 12h-24h.
[0027] In a third aspect, the present application provides an application of the above-mentioned single-ion conducting polyionic liquid electrolyte in a lithium-ion battery.
[0028] The single-ion conducting polyionic liquid electrolyte provided in the present application is mainly prepared from a borate anion receptor type crosslinker, a polyionic liquid monomer, a crystal plasticizer and a lithium salt, wherein the borate anion receptor type crosslinker is obtained by reacting a borate compound and an acrylate compound, the polyionic liquid monomer is composed of anions and cations, and the cation is one of imidazole, pyrrole and piperidine containing a carbon-carbon double bond, and the borate anion receptor type crosslinker and the cation of the polyionic liquid monomer are connected by a covalent bond.
[0029] By introducing borate anion receptor type cross-linking agents into polyionic liquid monomers, the presence of carbon-carbon double bonds on the polyionic liquid cations can copolymerize with the borate anion receptor type cross-linking agents. While the cations are polymerized and fixed, the Lewis acid action is used to fix the freely moving anions, effectively increasing the number of lithium ion migrations, thereby improving the high-rate performance of the battery. In addition, by using plasticizers, the room temperature ionic conductivity is increased, thereby improving the battery performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0031] Figure 1 This is a schematic diagram of a process of an embodiment of the preparation method in this application;
[0032] Figure 2 This is the ionic conductivity diagram of the single ion conducting polyionic liquid electrolyte of Example 1 of this application
[0033] Figure 3 The current / time test curve and the impedance test curve before and after polarization of the single ion conducting polyionic liquid electrolyte of Example 1 of the present application are shown;
[0034] Figure 4 This is the linear sweep voltammogram of the single ion conducting polyionic liquid electrolyte of Example 1 of the present application;
[0035] Figure 5 This is a cycle diagram of a battery using nickel cobalt manganese oxide NCM811 as the positive electrode and metallic lithium as the negative electrode at 0.3C in Example 1 of the present application. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and advantages of the present application clearer, the technical solution of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
[0037] The embodiment of the present application provides a single-ion conducting polyionic liquid electrolyte. By introducing a borate anion receptor type cross-linking agent into a polyionic liquid monomer, a carbon-carbon double bond exists on the polyionic liquid cation, which can copolymerize with the borate anion receptor type cross-linking agent. While the cation is polymerized and fixed, the Lewis acid action is used to fix the freely moving anions, effectively increasing the lithium ion migration number, thereby improving the high-rate performance of the battery, and solving the technical problem of too low lithium ion migration number of ionic liquid electrolytes in related technologies.
[0038] The single-ion conducting polyionic liquid electrolyte provided in the present application is mainly prepared from a borate anion receptor crosslinker, a polyionic liquid monomer, a crystal plasticizer and a lithium salt.
[0039] The borate anion receptor crosslinking agent is obtained by reacting a borate compound and an acrylate compound; the polyionic liquid monomer is composed of anions and cations, and the cation is one of imidazoles, pyrroles and piperidines containing a carbon-carbon double bond.
[0040] The borate anion receptor crosslinking agent and the cation of the polyionic liquid monomer are connected by a covalent bond.
[0041] In this embodiment, the borate anion receptor crosslinker and the anion of the polyionic liquid monomer are also connected by a covalent bond. Specifically, the borate anion receptor crosslinker and the anion of the polyionic liquid monomer are connected by a coordination bond.
[0042] The single-ion conducting polyionic liquid electrolyte of this embodiment combines a borate anion receptor crosslinker, a polyionic liquid monomer and a plasticizer to improve room temperature ionic conductivity and lithium ion migration number, thereby improving battery performance.
[0043] In some embodiments provided in the present application, the structural formula of the cation of the above-mentioned polyionic liquid monomer is:
[0044]
[0045] Wherein, R is methyl, ethyl, propyl or butyl, and n is 1-3.
[0046] Optionally, the anion of the polyionic liquid monomer is a bis(trifluoromethanesulfonyl imide) ion, a bis(fluorosulfonyl imide) ion, a hexafluorophosphate ion, or a tetrafluoroborate ion.
[0047] Preferably, the anion of the polyionic liquid monomer is a bis(trifluoromethanesulfonyl)imide ion.
[0048] In this embodiment, the cations in the polyionic liquid monomer can participate in polymerization, and the anions can be fixed by the borate anion receptor to achieve single ion conduction.
[0049] In some embodiments provided herein, the borate anion receptor crosslinker contains a boron oxygen bond (BO) and a carbon-carbon double bond (C=C), sp 2 Hybridized boron contains holes, which can interact electrostatically with anions in the system, further inhibiting anion migration and increasing the number of lithium ion migration.
[0050] The structural formula of the above-mentioned borate anion receptor type cross-linking agent is:
[0051]
[0052] Wherein, n is 1-10.
[0053] Furthermore, the borate ester compound is trimethyl borate or trimethoxyboroxine; and the acrylate compound is 2-hydroxyethyl methacrylate or polyethylene glycol methacrylate.
[0054] On the basis of the above-mentioned embodiment, in this embodiment, the molar ratio of the above-mentioned borate compound to the above-mentioned acrylate compound is 1:3.
[0055] In this embodiment, the synthesis of the borate anion receptor cross-linking agent is as follows: trimethyl borate (TMB) or trimethoxyboroxine (TMBX) is subjected to a substitution reaction with 2-hydroxyethyl methacrylate (HEMA) or polyethylene glycol methacrylate (PEGMA), and the molar ratio of trimethyl borate (TMB) or trimethoxyboroxine (TMBX) to 2-hydroxyethyl methacrylate (HEMA) or polyethylene glycol methacrylate (PEGMA) is 1:3.
[0056] Furthermore, in this embodiment, the molar ratio of the borate anion receptor crosslinker, the polyionic liquid monomer, the plasticizer and the lithium salt is in the range of 1:(1-9):2:1.
[0057] Preferably, the reaction molar ratio of the borate anion receptor crosslinker, the polyionic liquid monomer, the crystal plasticizer and the lithium salt is in the range of 1:5:2:1.
[0058] Furthermore, in this embodiment, the above-mentioned plasticizer is succinonitrile (SN); and the above-mentioned lithium salt is lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) or lithium bis(fluorosulfonyl)imide (LiFSI).
[0059] The present application provides a method for preparing a single-ion conducting polyionic liquid electrolyte, comprising the following steps:
[0060] In the absence of solvent, a borate anion receptor crosslinker, a polyionic liquid monomer, a plasticizer and a lithium salt are mixed, and in situ thermal polymerization is performed under the action of a thermal initiator to obtain a single ion conductive polyionic liquid electrolyte.
[0061] In some embodiments provided in the present application, the mass of the thermal initiator is 1%-5% of the total mass of the borate anion receptor cross-linking agent and the polyionic liquid monomer.
[0062] In this embodiment, the thermal initiator is azobisisobutyronitrile (AIBN).
[0063] Preferably, the reaction temperature of the in-situ thermal polymerization is 60° C.-80° C., and the reaction time is 12 h-24 h.
[0064] In this embodiment, a borate anion receptor cross-linking agent, a polyionic liquid monomer, a crystal plasticizer and a lithium salt are fully mixed, and in situ polymerization is performed under the action of a thermal initiator to form a cross-linked network structure. The polyionic liquid electrolyte prepared by in situ thermal polymerization is a single-ion conducting electrolyte. The preparation method has simple steps, is easy to synthesize, does not require the use of solvents, is compatible with existing lithium ion electrolyte processes, and is easy to prepare on an industrial scale.
[0065] like Figure 1 As shown, the present application embodiment also provides a method for preparing the above-mentioned single ion conducting polyionic liquid electrolyte, comprising the following steps:
[0066] Step S1. reacting a borate compound and an acrylate compound to prepare a borate anion receptor type crosslinker;
[0067] Step S2. Adding a borate anion receptor crosslinker, a polyionic liquid monomer, a plasticizer and a lithium salt into a vial, and adding a thermal initiator, and stirring to obtain a clear precursor solution;
[0068] Step S3. Place the positive electrode in the positive electrode shell of the button battery, drip the precursor solution in sequence, cover with a cellulose diaphragm, drip the precursor solution, place the lithium sheet, gasket, spring and negative electrode shell, and then pressure package, and then heat the battery at 60℃-80℃ for 12h-24h to obtain a single-ion conductive polyionic liquid electrolyte.
[0069] The embodiment of the present application also provides an application of a single-ion conducting polyionic liquid electrolyte in a lithium-ion battery.
[0070] In this embodiment, in a glove box, a borate anion receptor crosslinker, a polyionic liquid monomer, a plasticizer and a lithium salt are added to a vial in proportion, and a thermal initiator azobisisobutyronitrile is added and stirred for 3 hours to obtain a clear precursor solution. When assembling a lithium-ion battery, the precursor solution is added in situ to a separator, and the separator is one of cellulose, glass fiber (GFA), and polyethylene (PE).
[0071] The technical solution provided in this application is described in detail below in conjunction with the examples. If the manufacturer's brand or preparation method is not specified, the raw materials, equipment or solvents used are all common raw materials, equipment or solvents on the market. Unless otherwise specified, the raw materials of the same name used in the following examples and comparative examples are all the same raw materials.
[0072] Embodiment 1:
[0073] Example 1 of the present application provides a single ion conducting polyionic liquid electrolyte, and the preparation method thereof is as follows:
[0074] The first step is the preparation of a borate anion receptor crosslinker: 15 mmol of 2-hydroxyethyl methacrylic acid (HEMA) and 5 mmol of trimethyl borate (TMB) are dissolved in anhydrous acetonitrile, heated and stirred at 50°C in a glove box for 3 hours; then heated at 70°C for 3 hours under argon purge to remove byproduct methanol; then unreacted trimethyl borate and residual acetonitrile are removed by reduced pressure distillation at 65°C; finally, the product is vacuum dried for 48 hours and transferred to a glove box for storage to obtain a borate anion receptor crosslinker (BTETM);
[0075] The second step is the preparation of single ion conducting polyionic liquid electrolyte precursor: in a glove box, the obtained borate anion receptor crosslinker, 1-methyl-1-propylene pyrrolidine bis(trifluoromethanesulfonyl imide), succinonitrile (SN) and lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) are added into a vial in a molar ratio of 1:5:2:1, and azobisisobutyronitrile (AIBN) is added and stirred for 3 hours to obtain a clear precursor solution; the mass of azobisisobutyronitrile accounts for 2% of the total mass of the borate anion receptor crosslinker and 1-methyl-1-propylene pyrrolidine bis(trifluoromethanesulfonyl imide) monomers;
[0076] The third step is the preparation of single-ion conducting polyionic liquid electrolyte: in the glove box, place the positive electrode in the positive electrode shell of the button battery, drip the precursor solution in turn, cover with a cellulose diaphragm, drip the precursor solution, place the lithium sheet, gasket, shrapnel and negative electrode shell, and then pressure package, and then heat the battery at 70°C for 20 hours to obtain a single-ion conducting polyionic liquid electrolyte.
[0077] The single-ion conducting polyionic liquid electrolytes of Examples 2 to 7 are prepared in a similar manner to that of Example 1, except that the raw materials and proportions thereof, and the in-situ thermal polymerization reaction parameters are different. The specific differences are described below and in Table 1.
[0078] Example 2
[0079] In Example 2, except that when preparing the borate anion receptor type cross-linker, 15 mmol of 2-hydroxyethyl methacrylic acid (HEMA) and 5 mmol of 2,4,6-trimethoxyboroxane (TMBX) were dissolved in anhydrous acetonitrile, unreacted 2,4,6-trimethoxyboroxane and residual acetonitrile were removed by reduced pressure distillation at 65°C, and the borate anion receptor type cross-linker (TBTETM) was obtained, which was different from Example 1, the remaining steps and parameters were the same as Example 1.
[0080] Example 3
[0081] In Example 3, except that 15 mmol of polyethylene glycol methacrylate (PEGMA, Mw=360) and 5 mmol of trimethyl borate (TMB) were dissolved in anhydrous acetonitrile and a borate anion receptor type crosslinker (LBC) was obtained, the mass of azobisisobutyronitrile accounted for 1% of the total mass of the borate anion receptor type crosslinker and the polyionic liquid monomer, and the battery was heated at 80°C for 12 hours for polymerization, which was different from Example 1, the remaining steps and parameters were the same as Example 1.
[0082] Example 4
[0083] In Example 4, except that 1-propylene-3-methylimidazole bis(trifluoromethanesulfonyl)imide salt is selected as the polyionic liquid monomer during the preparation of the single ion conducting polyionic liquid electrolyte precursor, which is different from Example 1, the remaining steps and parameters are the same as those of Example 1.
[0084] Example 5
[0085] In Example 5, except that the polyionic liquid monomer is selected as 1-propylene-4-methylpiperidinium bistrifluoromethanesulfonyl imide salt, the mass of azobisisobutyronitrile accounts for 5% of the total mass of the borate anion receptor cross-linker and the polyionic liquid monomer, and the battery is heated and polymerized at 60°C for 24 hours, which is different from Example 1, the remaining steps and parameters are the same as Example 1.
[0086] Example 6
[0087] In Example 6, except that the obtained borate anion receptor crosslinker, 1-methyl-1-propenylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, succinonitrile (SN) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were added in a molar ratio of 1:1:2:1, which is different from Example 1, the other steps and parameters are the same as Example 1.
[0088] Example 7
[0089] In Example 7, except that the obtained borate anion receptor crosslinker, 1-methyl-1-propenylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, succinonitrile (SN) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were added in a molar ratio of 1:9:2:1, which is different from Example 1, the other steps and parameters are the same as Example 1.
[0090] Comparative Example 1
[0091] Step 1: Preparation of electrolyte precursor: In a glove box, 1-methyl-1-propenylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, succinonitrile (SN) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were added into a vial at a molar ratio of 6:2:1, and 2% of azobisisobutyronitrile (AIBN) by weight of 1-methyl-1-propenylpyrrolidine bis(trifluoromethanesulfonyl)imide salt monomer was added, and stirred for 3 hours to obtain a clear precursor solution;
[0092] The second step is electrolyte preparation: in a glove box, place the positive electrode in the positive electrode shell of the button battery, add the precursor liquid in turn, cover with a cellulose diaphragm, add the precursor liquid, place the lithium sheet, gasket, shrapnel and negative electrode shell, then pressure package, and finally heat the battery at 70°C for 20 hours to obtain a polymer electrolyte.
[0093] Comparative Example 2
[0094] The first step is electrolyte precursor preparation: in a glove box, the prepared BTETM, succinonitrile (SN) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) are added into a vial at a molar ratio of 6:2:1, and 2% of azobisisobutyronitrile (AIBN) by mass of BTETM is added and stirred for 3 h to obtain a clear precursor solution;
[0095] The second step is the preparation of single-ion conducting polyionic liquid electrolyte: in a glove box, place the positive electrode in the positive electrode shell of the button battery, drip the precursor liquid in turn, cover with a cellulose diaphragm, drip the precursor liquid, place the lithium sheet, gasket, shrapnel and negative electrode shell, and then pressure package, and then heat the battery at 70°C for 20 hours to obtain a single-ion conducting polyionic liquid electrolyte.
[0096] Comparative Example 3
[0097] Step 1: Preparation of electrolyte precursor: In a glove box, the prepared BTETM, 1-methyl-1-propylene pyrrolidine bis(trifluoromethanesulfonyl)imide salt and bis(trifluoromethanesulfonyl)imide lithium (LiTFSI) were added into a vial at a molar ratio of 1:5:0.75, and azobisisobutyronitrile (AIBN) was added, and the azobisisobutyronitrile (AIBN) accounted for 2% of the total mass of BTETM and 1-methyl-1-propylene pyrrolidine bis(trifluoromethanesulfonyl)imide salt monomers, and stirred for 3 hours to obtain a clear precursor solution;
[0098] The second step is the preparation of single-ion conducting polyionic liquid electrolyte: in a glove box, place the positive electrode in the positive electrode shell of the button battery, drip the precursor liquid in turn, cover with a cellulose diaphragm, drip the precursor liquid, place the lithium sheet, gasket, shrapnel and negative electrode shell, and then pressure package, and then heat the battery at 70°C for 20 hours to obtain a single-ion conducting polyionic liquid electrolyte.
[0099] Comparative Example 4
[0100] Step 1: Preparation of electrolyte precursor: In a glove box, the prepared BTETM, 1-methyl-1-propylene pyrrolidine bis(trifluoromethanesulfonyl)imide salt, succinonitrile (SN) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were added into a vial at a molar ratio of 1:0.5:2:1, and 2% of azobisisobutyronitrile (AIBN) based on the total mass of BTETM and 1-methyl-1-propylene pyrrolidine bis(trifluoromethanesulfonyl)imide salt monomers was added, and stirred for 3 hours to obtain a clear precursor solution;
[0101] The second step is the preparation of single-ion conducting polyionic liquid electrolyte: in a glove box, place the positive electrode in the positive electrode shell of the button battery, drip the precursor liquid in turn, cover with a cellulose diaphragm, drip the precursor liquid, place the lithium sheet, gasket, shrapnel and negative electrode shell, and then pressure package, and then heat the battery at 70°C for 20 hours to obtain a single-ion conducting polyionic liquid electrolyte.
[0102] Comparative Example 5
[0103] In Comparative Example 5, except that the molar ratio is 1:9.5:2:1, which is different from Example 1, the remaining steps and parameters are the same as those of Comparative Example 4.
[0104] Table 1 Parameter list
[0105]
[0106]
[0107] In Table 1, the molar ratio is the molar ratio of the borate anion receptor type cross-linker, the polyionic liquid monomer, the crystal plasticizer and the lithium salt. There is no borate anion receptor type cross-linker in Comparative Example 1, so its molar ratio is the molar ratio of the polyionic liquid monomer, the crystal plasticizer and the lithium salt. Similarly, the molar ratio in Comparative Example 2 is the molar ratio of the borate anion receptor type cross-linker, the crystal plasticizer and the lithium salt, and the molar ratio in Comparative Example 3 is the molar ratio of the borate anion receptor type cross-linker, the polyionic liquid monomer and the lithium salt.
[0108] The electrolytes of Examples 1-7 and Comparative Examples 1-5 were tested for ionic conductivity, lithium ion migration number and point chemical window. The test results are shown in Table 2.
[0109] like Figure 2-Figure 4 As shown, the single ion conducting polyionic liquid electrolyte of Example 1 of the present application has a conductivity of 7.63×10 -4 , the lithium ion transfer number is 0.70, and the electrochemical window is 5.5V. Figure 5 As shown, the single-ion conducting polyionic liquid electrolyte of Example 1 can match the high-voltage nickel cobalt manganese oxide lithium NCM811 positive electrode and stably cycle 50 cycles at a current of 0.3C without capacity decay.
[0110] Table 2 Test results
[0111]
[0112]
[0113] It can be seen from the data of Examples 1-7 that as the content of polyionic liquid monomer increases, the lithium ion migration number gradually decreases, while the electrochemical window slightly increases, and reaches a more balanced state when the molar ratio of the borate anion receptor crosslinker, polyionic liquid monomer, plasticizer and lithium salt reaction is in the range of 1:5:2:1.
[0114] It can be seen from the data of Example 1 and Comparative Example 1 that if there is no borate anion receptor crosslinker in the system, the lithium ion migration number of the electrolyte will be greatly reduced, indicating that BTETM can effectively fix anions in the system, thereby improving the lithium ion migration number.
[0115] It can be seen from the data of Example 1 and Comparative Example 2 that without adding polyionic liquid, the ionic conductivity is slightly reduced, and the electrochemical window is reduced from 5.5V to 4.3V, indicating that the presence of polyionic liquid can greatly improve the antioxidant property of the system.
[0116] It can be seen from the data of Example 1 and Comparative Example 3 that after adding the plasticizer, the strong polar chemical bonds in succinonitrile coordinate with the lithium salt to promote the dissociation of the lithium salt, thereby significantly improving the ionic conductivity.
[0117] It can be seen from the data of Example 1, Comparative Example 4 and Comparative Example 5 that the proportion of polyionic liquid monomer is too low, the electrochemical window is insufficient, and it cannot effectively match the high-voltage positive electrode material, indicating that too low a proportion of polyionic liquid will significantly affect the electrochemical stability of the system; if the proportion of polyionic liquid monomer is too high, the lithium ion migration number will drop sharply, and a significant reduction in the lithium ion migration number will produce serious concentration polarization, resulting in impaired battery performance. Therefore, the polyionic liquid monomer needs to meet an appropriate proportion.
[0118] The above results illustrate that the single-ion conducting polymer electrolyte prepared by using borate anion receptor crosslinker, polyionic liquid monomer, plasticizer and lithium salt can significantly improve the ionic conductivity, lithium ion migration number and electrochemical window by utilizing the characteristics of different monomers and the synergistic effect between different monomers, thereby improving battery performance.
[0119] In the description of this specification, the description with reference to the terms "one embodiment / method", "some embodiments / methods", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment / method or example are included in at least one embodiment / method or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment / method or example. Moreover, the specific features, structures, materials or characteristics described may be combined in a suitable manner in any one or more embodiments / methods or examples. In addition, those skilled in the art may combine and combine the different embodiments / methods or examples described in this specification and the features of the different embodiments / methods or examples, unless they are contradictory.
[0120] It should be noted that, in the present application, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements defined by the sentence "comprise one..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements. In the present application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically stipulated.
[0121] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A single ion conducting polyionic liquid electrolyte, characterized in that: It is mainly prepared from borate anion receptor crosslinker, polyionic liquid monomer, crystal plasticizer and lithium salt; The borate anion receptor crosslinking agent is obtained by reacting a borate compound and an acrylate compound; The polyionic liquid monomer is composed of anions and cations, and the cation is one of imidazoles, pyrroles, and piperidines containing a carbon-carbon double bond; The borate anion receptor crosslinker and the cation of the polyionic liquid monomer are linked by covalent bonds.
2. The single-ion conducting polyionic liquid electrolyte according to claim 1, characterized in that: The structural formula of the cation of the polyionic liquid monomer is: Wherein, R is methyl, ethyl, propyl or butyl, and n is 1-3.
3. The single-ion conducting polyionic liquid electrolyte according to claim 1, characterized in that: The structural formula of the borate anion receptor cross-linking agent is: Wherein, n is 1-10.
4. The single-ion conducting polyionic liquid electrolyte according to claim 3, characterized in that: The borate ester compound is trimethyl borate or trimethoxyboroxine; The acrylate compound is 2-hydroxyethyl methacrylate or polyethylene glycol methacrylate.
5. The single-ion conducting polyionic liquid electrolyte according to claim 1 or 4, characterized in that: The molar ratio of the borate compound to the acrylate compound is 1:
3.
6. The single-ion conducting polyionic liquid electrolyte according to claim 1, characterized in that: The molar ratio of the borate anion receptor crosslinking agent, the polyionic liquid monomer, the crystal plasticizer and the lithium salt is in the range of 1:(1-9):2:
1.
7. The single-ion conducting polyionic liquid electrolyte according to claim 1, characterized in that: The crystal plasticizer is succinonitrile; The lithium salt is lithium bis(trifluoromethanesulfonyl imide) or lithium bis(fluorosulfonyl imide); The anion of the polyionic liquid monomer is a bis(trifluoromethanesulfonyl imide) ion, a bis(fluorosulfonyl imide) ion, a hexafluorophosphate ion, or a tetrafluoroborate ion.
8. A method for preparing the single-ion conducting polyionic liquid electrolyte according to any one of claims 1 to 7, characterized in that: The method comprises: In the absence of solvent, a borate anion receptor crosslinker, a polyionic liquid monomer, a plasticizer and a lithium salt are mixed, and in situ thermal polymerization is performed under the action of a thermal initiator to obtain a single ion conductive polyionic liquid electrolyte.
9. The preparation method according to claim 8, characterized in that: The mass of the thermal initiator is 1%-5% of the total mass of the borate anion receptor crosslinker and the polyionic liquid monomer; The reaction temperature of the in-situ thermal polymerization is 60° C.-80° C., and the reaction time is 12 h-24 h.
10. Use of the single-ion conducting polyionic liquid electrolyte according to any one of claims 1 to 7 in a lithium-ion battery.
